As transformações no mundo do trabalho e o futuro do seguro-desemprego no Brasil - José Paulo Zeetano Chahad (Economia Aplicada, 2000)
This paper deals with the Brazilian unemployment insurance system in relation to the transformations taking place in the labor market, as well as to the need to integrate this instrument to other labor related public policies. Based on the international experience, a consolidation ofthe Public Employment System is proposed, following the lines of Convention number 88, of the International Labor Organization. The system must integrate all government actions needed to improve the work of the unemployment insurance mechanism. It must take into account the operating parameters determined by the market, as well as be submitted to continuous performance evaluation, in a way as to improve efficiency and efficacy in labor market.